Evaluation of banana (latundan) as bait for marine crabs. - Macario, Angelo Constancia (Iloilo City University of the Philippines in the Visayas, 2013)
Overripe banana (latundan) was combined with fish Apogonlinealus and tested as bait for luring marine crabs to explore measures of reducing baiting cost, to find appropriate timing for crabbing, and to assess the applicability of banana to fish combination in catching marine crabs in association with crab pots. Four (4) bait treatments were used to complete the study, namely : no bait (BB), banana (BB), fish (FB), and banana-fish combination (FB+) ; ripeness stages of banana were also evaluated. Banana-fish baits obtained comparable results with fish baits. Moreover, pots with banana-fish bait exhibited high catching performance in shallow.with banana only caught the fewest crabs or smallest biomass. Laboratory experiments using various percentages of stimuli mixture from banana and fish combinations revealed significant differences relative to the negative control stimuli (p<0.05). Addition of banana up to 75% bait to fish can still elicit feeding responses by crabs. Confirmatory field experiments give similar results, which are important because they suggest that the addition of banana to fish bait can potentially reduce the expenses of panngal fishermen. Therefore, the use of banana combined with fish as bait can be help sustain the profits of these fishermen.
Thesis (M.S. Fisheries-Fisheries Biology)--[Miagao, Iloilo] : University of the Philippines in the Visayas, March 2013.
Keywords: Banana; Bait; Marine Crabs